Chronological Assessment of the Balta Alba Kurgan Loess-Paleosol Section (Romania) – A Comparative Study on Different Dating Methods for a Robust and Precise Age Model - Scheidt, Stephanie; Berg, Sonja; Hambach, Ulrich; Klasen, Nicole; Pötter, Stephan; Stolz, Alexander; Veres, Daniel; Zeeden, Christian; Brill, Dominik; Brückner, Helmut; Kusch, Stephanie; Laag, Christian; et al. (Frontiers in Earth Science, 2021)
Loess-paleosol sequences (LPSs) are important terrestrial archives of paleoenvironmental and paleoclimatic information. One of the main obstacles for the investigation and interpretation of these archives is the uncertainty of their age-depth relationship. In this study, four different dating techniques were applied to the Late Pleistocene to Holocene LPS Balta Alba Kurgan (Romania) in order to achieve a robust chronology. Luminescence dating includes analysis of different grain-size fractions of both quartz and potassium feldspar and best results are obtained using fine-grained quartz blue stimulated and polymineral post-infrared infrared stimulated luminescence measurements. Radiocarbon (14C) dating is based on the analysis of bulk organic carbon (OC) and compound-specific radiocarbon analysis (CSRA). Bulk OC and leaf wax-derived n-alkane 14C ages provide reliable age constraints for the past c. 25-27 kyr CSRA reveals post-depositional incorporation of roots and microbial OC into the LPS limiting the applicability of 14C dating in older parts of the sequence. Magnetic stratigraphy data reveal good correlation of magnetic susceptibility and the relative paleointensity of the Earth’s magnetic field with one another as well as reference records and regional data. In contrast, the application of paleomagnetic secular variation stratigraphy is limited by a lack of regional reference data. The identification of the Campanian Ignimbrite/Y-5 tephra layer in the outcrop provides an independent time marker against which results from the other dating methods have been tested. The most accurate age constraints from each method are used for two Bayesian age-depth modeling approaches. The systematic comparison of the individual results exemplifies the advantages and disadvantages of the respective methods. Although the two age-depth models agree very well, our study also demonstrates that the multi-method approach can improve the accuracy and precision of dating loess sequences.